Copolyesters based on poly(butylene terephthalate)s containing cyclohexyl and cyclopentyl ring: Effect of molecular structure on thermal and crystallization behavior - Sandhya, T. E.; Ramesh, C.; Sivaram, S. (Macromolecules, 2007)
In an effort to understand the role of molecular structure on the thermal properties of polyesters and copolyesters, the following polyesters were synthesized: poly(1,4-cyclohexane dimethylene terephthalate) (PCT), poly(butylene-1,4-cyclohexane dicarboxylate) (PBCD), poly (1,3-cyclopentane dimethylene terephthalate) (PCPDT), and poly(butylene-1,3-cyclopentane dicarboxylate) (PBCP). PCT and PCPDT are semicrystalline polymers with crystallization and melting temperatures higher than poly(butylene terephthalate) (PBT). However, PBCD and PBCP have lower glass transition temperature than PBT. From these homopolymers a series of poly(butylene-co-1,4-cyclohexane dimethylene terephthalate) (P(BT-co-CT )), poly(butylene terephthalate-co-1,4cyclohexane dicarboxylate) (P(BT-co-BCD)), poly(butylene-co-1,3-cyclopentylene dimethylene) (P(BT-co-CPDT)), and poly(butylene terephthalate-co-1,3-cyclopentane dicarboyxlate) (P(BT-co-PBCP)) random copolyesters were synthesized for the first time, and their cocrystallization behavior was investigated using differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The copolymers were found to be statistically random and crystallized in all compositions. The P(BT-co-CT) and (P(BT-co-CPDT) copolyesters exhibited typical eutectic behavior in melting and crystallization, which indicated isodimorphic cocrystallization behavior. On the other hand, in the case of P(BT-co-BCD) and P(BT-co-PBCP) copolymers, the melting and crystallization temperatures showed linear dependency with composition, indicating isomorphic-like crystallization behavior.